2008
DOI: 10.1007/s00109-008-0423-2
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal cysteine peptidase cathepsin L protects against cardiac hypertrophy through blocking AKT/GSK3β signaling

Abstract: The lysosomal cysteine peptidase cathepsin L (CTSL) is an important lysosomal proteinase involved in a variety of cellular functions including intracellular protein turnover, epidermal homeostasis, and hair development. Deficiency of CTSL in mice results in a progressive dilated cardiomyopathy. In the present study, we tested the hypothesis that cardiac overexpression of human CTSL in the murine heart would protect against cardiac hypertrophy in vivo. The effects of constitutive human CTSL expression on cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
66
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 23 publications
2
66
1
Order By: Relevance
“…In contrast, the mRNA and protein levels of Cat S are markedly increased in rats or humans with hypertension-induced heart failure, suggesting that Cat S participates in pathological LV remodeling by mediating ECM degradation in cooperation with the MMPs. Tang et al [22] found that overexpression of cathepsin L inhibits cardiac hypertrophy and fibrosis by blocking Akt/GSK3beta signaling. Blocking the angiotensin II type 1 receptor was reported [20] to attenuate cardiac remodeling and dysfunction by inhibiting the expression and activity of cathepsin.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the mRNA and protein levels of Cat S are markedly increased in rats or humans with hypertension-induced heart failure, suggesting that Cat S participates in pathological LV remodeling by mediating ECM degradation in cooperation with the MMPs. Tang et al [22] found that overexpression of cathepsin L inhibits cardiac hypertrophy and fibrosis by blocking Akt/GSK3beta signaling. Blocking the angiotensin II type 1 receptor was reported [20] to attenuate cardiac remodeling and dysfunction by inhibiting the expression and activity of cathepsin.…”
Section: Discussionmentioning
confidence: 99%
“…These and other transcription factor substrates are also important in the heart. The CTSL-related effects shown by Tang et al [5] remain imperfectly defined. NF-κB could be involved; however, this hypothesis needs to be tested further.…”
mentioning
confidence: 96%
“…Tang et al [5], in this issue, pursue variations on this theme further. They overexpressed human CTSL in the mouse heart.…”
mentioning
confidence: 99%
See 2 more Smart Citations